REPRESENTASI BUDAYA LOKAL PADA LEGENDA DANAU TOBA DI ERA DIGITAL - Siregar, Musbar Soleman; Nirmawan, Nirmawan (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This research aims to analyze the representation of local culture in the Legend of Lake Toba as presented through blog media in the digital era. The background of this study is rooted in concerns about the potential reduction of cultural values in the process of digitizing folktales, as well as the importance of preserving local cultural identity amid globalization and the advancement of information technology. The research employs a descriptive-analytical qualitative approach, with primary data consisting of two versions of the Legend of Lake Toba: the original text version and the digital version from the blog